Ethics and epidemiology - Coughlin, Steven S. (Steven Scott), 1957-; Beauchamp, Tom L.; Weed, Douglas L., 1952- (New York ; Oxford : Oxford University Press, 2009)
Written by epidemiologists, ethicists and legal scholars, this book provides an in-depth account of the moral problems that often confront epidemiologists, including both theoretical and practical issues.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Epidemiology -- Moral and ethical aspects